Teacher's commitment, self-efficacy and job satisfaction as communicated by trained teachers - Mokhtar, Aida; Maouloud, Vatimetou Mokhtar; Omowunmi, Asafa Kafayat; Nordin, Mohamad Sahari (SAGE Publication, 2021)
The aim of the paper is to establish the mediating role of teachers’ self-efficacy in the relationship between teachers’ job satisfaction and teachers’ commitment of primary school teachers in Malaysia. Although several scholars have established the relationship between teachers’ commitment and job satisfaction, this is the first study that tests the mediating effect of selfefficacy in the relationship of job satisfaction and teachers’ commitment in primary schools in Malaysia using motivationhygiene theory. The research study used a validated questionnaire on a sample of 984 teachers and the research questions in the study were addressed by using structural equation modelling. The findings were that self-efficacy significantly mediated the relationship between primary school teachers’ commitment and job satisfaction, both teachers’ commitment and selfefficacy had significant and direct impacts on the job satisfaction of primary school teachers and the presence of self-efficacy enhanced teachers’ commitment and improved the job satisfaction of primary school teachers in Malaysia. It is clear that teachers needed to be communicated on the importance of having greater self-efficacy for better commitment and job satisfaction. As the study used a cross-sectional research design that was quantitative-oriented, in future, interviews could be adopted for a more inductive examination of teachers’ job satisfaction, self-efficacy and commitment. The primary schools in Malaysia should consider the role of self-efficacy in improving job satisfaction among teachers in Malaysia by adopting strategies that would enhance teachers’ self-efficacy so as to spur them to perform better at their jobs